TEOLOGI KRISTEN DALAM REVOLUSI INDUSTRI 4.0: Dampak Teknologi pada Komunitas Iman dan Pemberitaan Injil - Welsiana Kandun; Perawati, Agustina Ruru, Firdayanti, Iramaya (ADISAM PUBLISHER, 2025)
This research aims to analyze and explore the impact of the Fourth Industrial Revolution, characterized by the development of advanced technologies such as artificial intelligence (AI), the internet of things (IoT), and big data, on Christian theology, particularly in the context of faith communities and evangelism. By employing a literature review method, this study examines various relevant sources, including academic articles, books, and research reports, to understand how technology has transformed worship practices, social interactions, and evangelistic strategies within the church. The findings indicate that although technology offers new opportunities to expand the reach of evangelistic missions through social media and digital platforms, ethical and spiritual challenges also arise, such as the loss of depth in community relationships and the risk of diminished spiritual experiences. This research provides important insights for churches and Christian leaders in responding to the challenges and opportunities presented by technological developments, aiming to preserve the essence of spirituality while remaining relevant in an increasingly digitally connected world